Enhanced neonatal Fc receptor function improves protection against primate SHIV infection - Ko, Sung-Youl; Pegu, Amarendra; Rudicell, Rebecca S.; Yang, Zhi-yong; Joyce, M. Gordon; Chen, Xuejun; Wang, Keyun; Bao, Saran; Kraemer, Thomas D.; Rath, Timo; Zeng, Ming; Schmidt, Stephen D.; et al. (Nature (London), 2014)
A mutation in VRC01, a broadly neutralizing, HIV-1-specific antibody, confers enhanced binding to the neonatal Fc receptor, increasing the antibody half-life in the serum and localization in mucosal tissues, where it provides superior protection against rectal simian HIV-1 infection in macaques. Enhanced anti-HIV activity in mutant VRC01 antibody The recent discovery of broad and potent anti-HIV-1 antibodies has renewed interest in their use for passive protection against human immunodeficiency virus-1 in humans. This paper describes a mutation in the HIV-specific broadly neutralizing antibody VRC01 that confers enhanced binding to the neonatal Fc receptor and increases the antibody half-life in serum and mucosal tissues. It conferred superior protection in a rectal simian-HIV challenge model in macaques when compared to wild-type VRC01. To protect against human immunodeficiency virus (HIV-1) infection, broadly neutralizing antibodies (bnAbs) must be active at the portals of viral entry in the gastrointestinal or cervicovaginal tracts. The localization and persistence of antibodies at these sites is influenced by the neonatal Fc receptor (FcRn) 1 , 2 , whose role in protecting against infection in vivo has not been defined. Here, we show that a bnAb with enhanced FcRn binding has increased gut mucosal tissue localization, which improves protection against lentiviral infection in non-human primates. A bnAb directed to the CD4-binding site of the HIV-1 envelope (Env) protein (denoted VRC01) 3 was modified by site-directed mutagenesis to increase its binding affinity for FcRn. This enhanced FcRn-binding mutant bnAb, denoted VRC01-LS, displayed increased transcytosis across human FcRn-expressing cellular monolayers in vitro while retaining FcγRIIIa binding and function, including antibody-dependent cell-mediated cytotoxicity (ADCC) activity, at levels similar to VRC01 (the wild type). VRC01-LS had a threefold longer serum half-life than VRC01 in non-human primates and persisted in the rectal mucosa even when it was no longer detectable in the serum. Notably, VRC01-LS mediated protection superior to that afforded by VRC01 against intrarectal infection with simian–human immunodeficiency virus (SHIV). These findings suggest that modification of FcRn binding provides a mechanism not only to increase serum half-life but also to enhance mucosal localization that confers immune protection. Mutations that enhance FcRn function could therefore increase the potency and durability of passive immunization strategies to prevent HIV-1 infection.